Toward understanding business student professional development engagement. Issue 3 (3rd April 2017) - Blau, Gary; Blessley, Misty; Kunkle, Matthew; Schirmer, Michael; Regan, Laureen
ABSTRACT: Professional development engagement (PDE) is defined as the level of perceived undergraduate engagement in professional development activities. An 11-item measure of PDE exhibited a good reliability. Using a complete data sample of 467 graduating business undergraduates, four variable sets (student background or precollege variables, college-related variables, organization-related variables, and motivation-related variables) each explained significant incremental variance in PDE. Significant individual correlates of PDE included joining a student professional organization and motivation to attend business school. One outcome suggests that business schools need to leverage technology more aggressively to deliver professional development content both asynchronously and synchronously to more of their undergraduates.